1973
DOI: 10.1085/jgp.61.3.361
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Description of Sodium and Potassium Currents and Computed Action Potentials in Myxicola Giant Axons

Abstract: An analysis of the sodium and potassium conductances of Myxicola giant axons was made in terms of the Hodgkin-Huxley m, n, and h variables. The potassium conductance is proportional to n 2 . In the presence of conditioning hyperpolarization, the delayed current translates to the right along the time axis. When this effect was about saturated, the potassium conductance was proportional to n. The sodium conductance was described by assuming it proportional to mah. There is a range of potentials for which rh and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
88
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 25 publications
14
88
0
Order By: Relevance
“…The resulting activation time course of sodium currents is best described by the cube of an exponential function (the m 3 function). Subsequent studies in large peripheral axons confirmed that sodium currents activate after a delay (Goldman and Schauf, 1973;Keynes and Rojas, 1976;Neumcke et al, 1976;Neumcke and Stampfli, 1982). In all of these experiments, the time course of sodium current activation was best fit with the m n function in which n varied from 2 to 4, implying the presence of two to four independent identical gates.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The resulting activation time course of sodium currents is best described by the cube of an exponential function (the m 3 function). Subsequent studies in large peripheral axons confirmed that sodium currents activate after a delay (Goldman and Schauf, 1973;Keynes and Rojas, 1976;Neumcke et al, 1976;Neumcke and Stampfli, 1982). In all of these experiments, the time course of sodium current activation was best fit with the m n function in which n varied from 2 to 4, implying the presence of two to four independent identical gates.…”
Section: Introductionmentioning
confidence: 78%
“…Although several papers reported data on sodium current activation and deactivation time constants in central neurons (for example, Mainen et al, 1995;Martina and Jonas, 1997), none of them attempted to identify the shape of the activation time course of the current as it was done for the sodium currents recorded in the large peripheral axons (Goldman and Schauf, 1973;Keynes and Rojas, 1976;Neumcke et al, 1976;Neumcke and Stampfli, 1982). This fact could have several explanations.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence ofgallamine, the decline in INa during step depolarizations is a single exponential in Myxicola at all voltages (Goldman & Schauf, 1973), with r,'h at 5 'C decreasing from 2-0 msec at -40 mV to approximately 1 0 msec at +40 mV. For membrane potentials between -40 and -10 mV, the primary effect of gallamine was to slow Na+ inactivation (record at -20 mV in Fig.…”
Section: Effects Of Gallamine On Na+ Activationmentioning
confidence: 87%
“…The gating subunits are identical and independent of each other. Although the basic idea of charged groups translating (or rotating) to gate the channel opening/closing processes when the electric field is changed has been successfully applied to a variety of excitable membranes, there is evidence that Hodgkin-Huxley models in their simplest form fail to account for some of the kinetic properties of K+ and Na+ currents in different tissues (Goldman & Schauf, 1973;Palti, Ganot & Staimpfli, 1976;Bezanilla & Armstrong, 1977;Begenisich, 1979).…”
Section: Introductionmentioning
confidence: 99%